High power plasma interaction with tungsten grades in ITER relevant conditions. (March 2015) - Garkusha, E; Makhlaj, V A; Aksenov, N N; Byrka, O V; Malykhin, S V; Pugachov, A T; Bazylev, B; Landman, I; Pinsuk, G; Linke, J; Wirtz, M; Sadowski, M J; et al.
Abstract: Experimental simulations of ITER-like transient events with relevant surface heat load parameters (energy density up to 1.1 MJ/m 2 and the pulse duration of 0.25 ms) as well as particle loads (varied in wide range from 10 23 to 10 27 ion/m 2 s) were carried out with a quasistationary plasma accelerator QSPA Kh-50. Particular attention was paid to elaboration of damage of tungsten as a main candidate material for ITER divertor surfaces and also as prospective material for DEMO design. Erosion features, cracks evolution and changes in their thickness with increasing exposition dose are studied for different W grades, including deformed material with elongated grains, as well as WTa5 and sintered tungsten.